ANALISIS FAKTOR - FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM MEMBELI SEPEDA MOTOR YAMAHA PADA CV. FORTUNA ABADI MOTOR YAMAHA SEMITAU KAPUAS HULU - B11108056, Pipi Anita (Jurnal Manajemen Update, 2013)
Research is called factors analysis under consideration consumers in buying Yamaha motorcycle on CV. Fortuna Perennial Motor Yamaha Semitau Kapuas Hulu. The the problem in this research is factors anything considered consumers in buying Yamaha on CV. Fortuna Perennial Motor Yamaha Semitau Kapuas Hulu during this time. The purpose of this research is to find out what factors are considered consumers in buying motorcycles Yamaha on CV. Fortuna Perennial Motor Yamaha in Semitau. This research using a method of surveying with the object research on CV. Fortuna Perennial Motor Yamaha Semitau and the its consumers with a sample of as many as 100 people of respondents. The technique of collecting data: observation, interviews and kusioner. The analysis tools used are descriptive statistics that is getting an idea of what factors most considered consumers in buying Motorcycles Yamaha on CV. Fortuna Perennial Yamaha Semitau Kapuas Hulu, as well as to identify the characteristics of each variable in the form of a percentage then pulled his conclusion. The results of this research are considered consumer products very factor in buying vehicles Yamaha motorcycle on CV. Fortuna Perennial Yamaha Semitau Kapuas Hulu. The Authors provide recommendations that companies need more vigorous promotional activities through Television particularly Television West Kalimatan Ruai like TV, Radio, Newspapers and magazines because the media is more effective to convey a message. Should CV. Fortuna Perennial Motor Yamaha in Semitau give a period of an installment of a long to consumers that has been bought me a motorcycle on credit. Should an employee the front lines that meet and meet face-to-face directly with consumers ought to be friendly, more polite and provide information that is clear about motorcycles to consumers to come. Keywords: Consumer Purchasing Decisions